Using Airlifts to Collect and Concentrate Copepod Nauplii - Eric Cassiano; Matthew A. DiMaggio; Cortney Ohs; John Marcellus (EDIS)
Airlifts are simple and inexpensive and not new to aquaculture. The buoyancy of rising bubbles within a pipe or tube generates an upward flow of water that are often used as part of water treatment design in recirculating aquaculture systems, but can also be used to collect and concentrate live food organisms fed to marine fish larvae. Airlifts are more gentle and efficient than sieving. This 3-page fact sheet provides protocols and designs for harvesting and feeding copepod nauplii to marine fish larvae, but these methods can be adapted for use with many live feed organisms. Written by Eric Cassiano, Matthew DiMaggio, Cortney Ohs, and John Marcellus, and published by the UF Department of Fisheries and Aquatic Sciences, May 2015. (Photo credit: Jason S. Broach)